2013
DOI: 10.1371/journal.pone.0076192
|View full text |Cite|
|
Sign up to set email alerts
|

TCam-2 Seminoma Cells Exposed to Egg-Derived Microenvironment Modify Their Shape, Adhesive Pattern and Migratory Behaviour: A Molecular and Morphometric Analysis

Abstract: Seminoma is one of the most common Testicular Germ Cell Tumours that originates during embryonic development due to an alteration of the local niche that in turn results in a delayed or blocked differentiation of Primordial Germ Cells. The block of differentiation is actually a common way to develop cancer disease as postulated by the "embryonic rest theory of cancer". In agreement with this theory different studies have demonstrated that embryonic cues display the capacity of reprogramming aggressive cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Recently we showed similar structural and behavioural changes also in TCam-2 human seminoma cells, where EW was able to modulate seminoma cell phenotype and behaviour, by ensuring a proper set of morphogenetic signals [26].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Recently we showed similar structural and behavioural changes also in TCam-2 human seminoma cells, where EW was able to modulate seminoma cell phenotype and behaviour, by ensuring a proper set of morphogenetic signals [26].…”
Section: Introductionmentioning
confidence: 63%
“…We have previously shown that microenvironment derived from the albumen of unfertilized chicken eggs (EW, Egg White) dramatically modifies breast cancer cell architecture, and promotes the transition from a cancerous metabolomic profile (Warburg-like), towards an oxidative phenotype [25] . Recently we showed similar structural and behavioural changes also in TCam-2 human seminoma cells, where EW was able to modulate seminoma cell phenotype and behaviour, by ensuring a proper set of morphogenetic signals [26] .…”
Section: Introductionmentioning
confidence: 63%
“…Exposure of TCam-2 cells to s-microgravity deeply affects cell shape and architecture and induces microtubule disorientation and an increase in the actin microfilament network that increased the cell width, together with a transient collapse of the mechano-sensing microvilli-like structures. These peculiar cytoskeletal modifications have been proposed to be related to the autophagy process, which is postulated to be an adaptive cell response to s-microgravity, likely allowing the cell to survive in a modified physical microenvironment 24 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9,18,35 The trend FD assumed characterized well the migration process. Indeed, at earlier times of migration FD increase markedly, although not significantly, in both cell lines.…”
Section: Discussionmentioning
confidence: 99%